A systematic review of the effect of footwear, foot orthoses and taping on lower limb muscle activity during walking and running. (December 2019) - Reeves, Joanna; Jones, Richard; Liu, Anmin; Bent, Leah; Plater, Emma; Nester, Christopher
Background: External devices are used to manage musculoskeletal pathologies by altering loading of the foot, which could result in altered muscle activity that could have therapeutic benefits. Objectives: To establish if evidence exists that footwear, foot orthoses and taping alter lower limb muscle activity during walking and running. Study design: Systematic literature review. Methods: CINAHL, MEDLINE, ScienceDirect, SPORTDiscus and Web of Science databases were searched. Quality assessment was performed using guidelines for assessing healthcare interventions and electromyography methodology. Results: Thirty-one studies were included: 22 related to footwear, eight foot orthoses and one taping. In walking, (1) rocker footwear apparently decreases tibialis anterior activity and increases triceps surae activity, (2) orthoses could decrease activity of tibialis posterior and increase activity of peroneus longus and (3) other footwear and taping effects are unclear. Conclusion: Modifications in shoe or orthosis design in the sagittal or frontal plane can alter activation in walking of muscles acting primarily in these planes. Adequately powered research with kinematic and kinetic data is needed to explain the presence/absence of changes in muscle activation with external devices. Clinical relevance: This review provides some evidence that foot orthoses can reduce tibialis posterior activity, potentially benefitting specific musculoskeletal pathologies.